Studi Komparasi Strategi Cooperative Script Dan Jigsaw Terhadap Hasil Belajar Ipa Kelas Iv Sd Muhammadiyah 1 Surakarta Tahun 2015/2016 - Marseliana, Fransiska (2016)
This study aims to: (1) To determine differences in learning outcomes IPA fourth grade students of SD Muhammadiyah 1 Surakarta using Cooperative Script strategy using Jigsaw strategy. (2) To find a better strategy between Cooperative Script strategy with Jigsaw strategy for learning outcomes IPA fourth grade students of SD Muhammadiyah 1 Surakarta. This study included a quantitative study with an experimental model, subjects in the study are learners class IVB and IVC SD Muhammadiyah 1 Surakarta. The data collection technique using the techniques of tests and documentation. Test instruments include test the validity and reliability testing. Data were analyzed using t-test technique which preceded the prerequisite test analysis, the test of normality and homogeneity test. Based on data analysis with significance level of 5% was obtained < there are 0.266 <2.00172 and the average grade values obtained between classes using Cooperative Script strategy and classroom strategies that use Jigsaw strategy, namely 86,5 and 8,9. The conclusion of this study were (1) There is no difference in learning outcomes IPA fourth grade students of SD Muhammadiyah 1 Surakarta using Cooperative Script strategy using strategies Jigsaw year 2015/2016. (2) Cooperative Script strategy better than Jigsaw strategy on learning outcomes IPA fourth grade students of SD Muhammadiyah 1 Surakarta in 2015/2016. Keywords: Science Learning Outcomes, Cooperative Script Stategy, Strategy Jigsaw